2016
DOI: 10.1038/mtm.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

A scalable method for the production of high-titer and high-quality adeno-associated type 9 vectors using the HSV platform

Abstract: Recombinant adeno-associated vectors based on serotype 9 (rAAV9) have demonstrated highly effective gene transfer in multiple animal models of muscular dystrophies and other neurological indications. Current limitations in vector production and purification have hampered widespread implementation of clinical candidate vectors, particularly when systemic administration is considered. In this study, we describe a complete herpes simplex virus (HSV)-based production and purification process capable of generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 49 publications
4
61
0
Order By: Relevance
“…The virus titer of 1E10 PFU/ml is optimal, because the virus particles start to aggregate at 1E11 PFU/ml (as attested by high variance of the titer) and because preparations with a virus titer lower 1E8 PFU/ml are unstable over the years (data not shown). The overall recovery of 40% with our new purification strategy is comparable with or superior to those obtained in other virus/viral vector productions (Adamson-Small et al 2016; Merten et al 2016). …”
Section: Discussionsupporting
confidence: 70%
“…The virus titer of 1E10 PFU/ml is optimal, because the virus particles start to aggregate at 1E11 PFU/ml (as attested by high variance of the titer) and because preparations with a virus titer lower 1E8 PFU/ml are unstable over the years (data not shown). The overall recovery of 40% with our new purification strategy is comparable with or superior to those obtained in other virus/viral vector productions (Adamson-Small et al 2016; Merten et al 2016). …”
Section: Discussionsupporting
confidence: 70%
“…12 When DMEM was supplemented with 60 m M sodium chloride, there was a significant, 1.6- and 2.2-fold increase in rAAV vector genomes and transducing units, respectively (Fig. 4A and B, solid columns; p  < 0.05).…”
Section: Resultsmentioning
confidence: 88%
“…Similar to monoclonal antibodies, AAV is stable at acidic conditions, with no loss in infectivity of AAV9 when held for 2 hr at pH values between 2.5 and 8 (Potter et al, 2014). While infectivity remained, it was found that during an acid flocculation step of the harvest of AAV9 produced using HSV, HSV particles were undetectable (<100 pfu/ml) after the flocculation step (Adamson-Small et al, 2016).…”
Section: Viral Clearance Aspects Of Adventitious Agents Safety Evalmentioning
confidence: 95%